Strategi Peningkatan Kompetensi Penyuluh Agama Buddha di Era Society 5.0 - Siky Hendro Wibowo; Aris Budiyanto (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2023)
The emergence of the jargon of religious counselors as the spearhead of the Ministry of Religion is a logical consequence of expanding the role of  counseling in the community. In the midst of the rapid dynamics of the development of Indonesian society in the disruptive era, religious counselors have a strategic role in building mental, moral and piety values and also encouraging the improvement of the quality of life of religious communities in development. The Directorate General of Buddhist Community Guidance is challenged to have qualified human resources for Religious Counselors and to make Religious Counselors as a profession. In order to increase the competency and professionalism of human resources for Buddhist counselors, one of the strategic steps that can be taken is to involve the role and contribution of Buddhist Higher Education as the initiator of providing Professional Religion Counselors Education. This research is aimed to analyze the strategic for increasing the competence and professionalism of Buddhist Counselors through the initiation of the implementation of the Professional Education of Religious Counselors in the Society 5.0 era. The analysis used is SOAR analysis using the IFE-EFE matrix calculation. SOAR analysis is used as an analytical knife to examine external and internal factors that influence the readiness of Buddhist Higher Education as the initiator of implementing the Professional Education of Religious Counselors. Based on the results of the SOAR analysis, State Buddhist Religious Higher Education is in the OA strategy quadrant, namely benchmarking and designing the creation of an LMS (Learning Management System) which is the center for integration of all knowledge management and learning in PTKB and the development of Blended Learning in the context of implementing an independent learning education system Keywords: The Role of Buddhist Counselors; Competence; Higher Religious Education; Professional Education; SOAR Analysis; IFE-EFE Matrix.